The Role of Ultrasonography for Differentiating and Management of Malignant Cervical Lymph Nodes. Issue 1 (January 2016) - Dogan, Serap; Yildirim, Afra; Erbakirci, Refika; Okur, Aylin; Cagli, Sedat; Mavili, Ertugrul; Yuce, Imdat; Guney, Ercihan; Ozturk, Mustafa
No abstract available